The Differences in Bioactivity between Crude and Purified Cholera Toxin from Local Isolate of Vibrio cholera: Amina, N. Al- Thwani1 and Khlood, A. Al-Khafaji - Al- Thwani1, Amina N. (The Iraqi Journal of Veterinary Medicine, 2012)
In this investigate Cholera toxin was purified from the local clinical isolatedesignated as V. cholerae S . Few steps were employed for purification of CTincluding concentration of the protein, back extraction, and gel filtration. Thebioactivity of CT reflected that crude and purified toxin had lethal activity on Balb/cmice in which a dose of 2.5µg/ ml of purified toxin caused mice death withsymptoms such as muscle cramps and tachycardia while erythematous andinduration was seen at intradermal I. d injection of skin of Guinea pig.Histopathological examination for liver, intestine, adrenal gland and spleen of whitemice showed that liver tissue was more affected compared with spleen, intestine andadrenal gland tissues.